Software Quality Assurance Website Tenaga Kerja Non-Organik Menggunakan Standard ISO 9126 - Hesti Sukmawati (Teknik Komputer Politeknik Negeri Sriwijaya, 2022)
A website is beneficial for everyone in various aspects, especially in the world of work. Software quality assurance is one of the activities that use information technology in the world of work. PT Pupuk Sriwidjaja Palembang, commonly known as PT Pusri, is a subsidiary of PT Pupuk Indonesia (Persero). IT Service & Business Partner department is one of the departments that has an important role, such as managing all activities related to networking, computerization, and digital transformation. One of the websites created by IT Department is TKNO website. It is necessary to conduct a quality evaluation to create a high-quality website. This study aims to determine the quality of TKNO website using ISO 9126 standards and characteristics that have been adapted to the methods of TKNO website. The technique used in the measurement is different for each aspect tested so that it produces a value on the functionality aspect worth 3 (sufficient), usability aspects worth 0.89 (good), efficiency aspects worth 84.5% (good), and portability aspects worth 5 (very good).